Nest light environment and potential risk of cuckoo parasitism. - Muñoz-Gallego, Antonio Román; Altamirano-Jeschke, María; Takasu, Fugo; Nakamura, Hiroshi (My University, 2007)
Brood parasitism represents a significant cost in reproduction; thus, natural selection should favor the evolution of host defenses, which in turn may favor evolution of more sophisticated techniques by the parasite to overcome host defenses. These host defenses include egg rejection, attacking parasites near the nest, and avoiding parasitism by concealing nest sites. In all these antiparasitism strategies, nest light environment may play an important role. In the present study, the risk of Common Cuckoo (Cuculus canorus) parasitism for the Great Reed Warbler (Acrocephalus arundinaceus) was modeled in relation to the in situ nest light environment, from far ultraviolet (UV) to infrared (IR) radiation (280–1,100 nm), and nest situation and structure. The percentage of photosynthetically active radiation (PAR) plus IR radiation (400–1,100 nm) falling on the nest, maximum nest width, and distance between the nest and the nearest active conspecific neighbor were significantly related to the risk of parasitism. Photosynthetically active radiation alone explained 65% of variation in parasitism risk in the final model. Although solar radiation levels in nests were low (<4% for UV-B and UV-A radiation, 5% for PAR, and 22% for PAR plus IR radiation when cloudless), UV-B, UV-A, and visible-plus-IR radiation levels were significantly lower in nonparasitized nests. These findings provide the first evidence of a relationship between parasitism risk and nest concealment related to microhabitat light environment, with brighter nests suffering a higher risk of parasitism.
Keywords: Cucos - Parásitos; Aves - Nidos; Parasiticidas; Acrocephalus arundinaceus; Acrocephalus orientalis; Common Cuckoo; Antiparasitism defenses; Brood parasitism; Light environment; Ultraviolet radiation